ANALISIS GERAKAN BERULANG (REPETITIVE) DAN GETARAN LENGAN TANGAN (HAND ARM VIBRATION) TERHADAP KEJADIAN EPICONDYLITIS MEDIAL (GOLFER ELBOW) PADA PEKERJA MEUBEL PEMBUAT SPRINGBED BIGLAND PT. DAYAK LESTARI EKANIAGA - Deri, Deri; Pradana, Tedy Dian; Rossa, Idjeriah (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2015)
Golfer elbow or medial epicondylitis is irritation of the tendon that causes the tendon tears; the pronator teres muscle and flexor carpi radialis muscle. These are induced by the2repetitive movements, hand arm vibration and aggravated by the attitude of a static work. Also, lifting up the workload continuously and holding vibratory a working tool trigger this irritation.This study was aimed at analyzing the repetitive movement and hand arm vibration towards epicondylitis medial (golfer elbow) incidence among Bigland mattress makers at PT. Dayak Lestari EkaniagaAn observational method and a cross sectional approach were carried out in this study. The samples were 45 Bigland mattress makers. The data collecting technique employed primary and secondary data. While the data collecting tools used were stopwatch, hand arm vibratiaon meter (havm), questionnaires, observation sheets, scales, and tape measure.The study revealed that there were correlation of repetitive movement Pvalue=0,041, hand arm vibration Pvalue=0,017, and epicondylitis medial (golfer elbow) incidence.From the findings, the director of PT. Dayak Lestari Ekaniaga should minimize the risk of repetitive motion and hand arm vibration, such as tightening bolts or loosing ties on the machine. It can be done by conducting regular training, encouraging the workers to have exercise before working and providing Personal Protective Equipment or PPE. In addition, employees are expected to be more aware on the importance of controlling the dangers of repetitive movements and hand arm vibration. Least but not, further researchers are encourage to develop and accomplish this study.Key Words : (Repetitive), (Hamd Arm Vibration), (Golfer elbow).